IDENTIFIKASI SENYAWA ALFA-PINENE PADA MINYAK KAYU PUTIH MENGGUNAKAN FTIR - Rahayu, Cici (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Eucalyptus oil is an essential oil produced from the eucalyptus plant (Melaleuca cajuputi), which grows naturally in the Maluku Islands and northern Australia. This species has been widely developed in Indonesia, especially on the islands of Java and Maluku by utilizing the leaves and branches to be distilled traditionally by the community and commercially into essential oils with high economic value. Alpha-pinene is the largest composition contained in turpentine oil, which is around 70-95%. Alpha-pinene is an unsaturated hydrocarbon compound having 10 carbon atoms with the formula C10H16 is a colorless liquid with a characteristic odor. The structure of the alpha-pinene compound consists of two rings, namely cyclobutane and cyclohexene, therefore alpha-pinene is classified as bicyclic.